Association of Adverse Childhood Experiences and Resilience With Obesity, High Blood Pressure, and Parental Report of Behavioral Health Symptoms in Children: A Cross Sectional Study - Ashleigh Hall DO; Xandria West MA; Marilyn Brown MA; Erin Hall MD; Ella Kim MA; Alexa Leib MD; Paige Mergaman MD; Zanaib Salih MA; Stephen Aronoff MD (SAGE Publishing, 2023)
The interplay between Adverse Childhood Experiences (ACEs) and resilience on health in children is not well understood. Parents completed 3 questionnaires: ACEs, Child and Youth Resilience Measure (CYRM), and the Pediatric Symptom Checklist-17(PSC-17). BMI and blood pressure were measured. 19.8% of children had 4 or more ACEs, resilience ranged from 25 to 51, 14.3% had a positive PSC-17 score, 25.6% were obese, 3.1% had systolic hypertension, and 1.2% had diastolic hypertension. Higher ACEs (ACE OR: 1.398, 95% CI = 1.044-1.893, P  = .026) and lower resilience (Resilience OR: 0.740, 95% CI 0.668-0.812; P  = 1.13 × 10 −9 ) were predictive of increased reports of behavioral health symptoms, but not obesity or hypertension. The personal resilience subscale was a predictor of positive PSC-17 score (OR 0.646, 95% CI = 0.546-0.749, P  = 3.18 × 10 −8 ); relationship subscale was not. Cultivating resilience, especially personal aspects, may provide an effective intervention for behavioral health symptoms in children.